Increased Short-Term Beat-to-Beat QT Interval Variability in Patients with Impaired Glucose Tolerance - Orosz, Andrea; Baczkó, István; Nyiraty, Szabolcs; Körei, Anna E.; Putz, Zsuzsanna; Takács, Róbert; Nemes, Attila; Várkonyi, Tamás T.; Balogh, László; Ábrahám, György; Kempler, Péter; Papp, Julius Gy.; et al. (Frontiers in Endocrinology, 2017)
Prediabetic states and diabetes are important risk factors for cardiovascular morbidity and mortality. Determination of short-term QT interval variability (STVQT) is a non-invasive method for assessment of proarrhythmic risk. The aim of the study was to evaluate the STVQT in patients with impaired glucose tolerance (IGT). 18 IGT patients [age: 63 ± 11 years, body mass index (BMI): 31 ± 6 kg/m2, fasting glucose: 6.0 ± 0.4 mmol/l, 120 min postload glucose: 9.0 ± 1.0 mmol/l, hemoglobin A1c (HbA1c): 5.9 ± 0.4%; mean ± SD] and 18 healthy controls (age: 56 ± 9 years, BMI: 27 ± 5 kg/m2, fasting glucose: 5.2 ± 0.4 mmol/l, 120 min postload glucose: 5.5 ± 1.3 mmol/l, HbA1c: 5.4 ± 0.3%) were enrolled into the study. ECGs were recorded, processed, and analyzed off-line. The RR and QT intervals were expressed as the average of 30 consecutive beats, the temporal instability of beat-to-beat repolarization was characterized by calculating STVQT as follows: STVQT = Σ|QTn + 1 − QTn| (30x√2)−1. Autonomic function was assessed by means of standard cardiovascular reflex tests. There were no differences between IGT and control groups in QT (411 ± 43 vs 402 ± 39 ms) and QTc (431 ± 25 vs 424 ± 19 ms) intervals or QT dispersion (44 ± 13 vs 42 ± 17 ms). However, STVQT was significantly higher in IGT patients (5.0 ± 0.7 vs 3.7 ± 0.7, P < 0.0001). The elevated temporal STVQT in patients with IGT may be an early indicator of increased instability of cardiac repolarization during prediabetic conditions.